Increased levels of serum granzyme-B is associated with insulin resistance and increased cardiovascular risk in adolescent polycystic ovary syndrome patients. (March 2016) - Oztas, Efser; Ozler, Sibel; Tokmak, Aytekin; Yilmaz, Nafiye; Celik, Huseyin Tugrul; Kazancı, Fatmanur Hacıevliyagil; Danisman, Nuri; Ergin, Merve; Yakut, Halil Ibrahim
Abstract: Objectives: Our aim was to determine serum perforin and granzyme-B levels in adolescent PCOS patients, and to investigate whether they are associated with some of the insulin sensitivity, obesity and cardiovascular (CV) risk markers and metabolic syndrome. Study design: A case–control study was carried out including a total of 172 adolescents (83 PCOS patients and 89 age-matched healthy controls). Participants were recruited consecutively. Homeostasis model assessment (HOMA-IR), lipid parameters, and anthropometric measurements were determined. Serum perforin and granzyme B levels were measured by commercially available ELISA kits. HOMA-IR > 3.16 was considered to indicate the presence of insulin resistance. Logistic regression analysis was applied for the predictive value of granzyme-B for increased CV risk in PCOS patients. Results: As body mass index (BMI) of the PCOS patients was significantly higher than the controls (median 24.6 kg/m 2 and 21.4 kg/m 2, respectively, p < 0.001) all parameters were evaluated after adjustment for BMI. Adolescents with PCOS had significantly higher levels of fasting glucose, insulin, HOMA-IR and granzyme-B when compared with controls. According to the results of logistic regression analysis, granzyme-B levels were found to be significantly associated with increased HOMA-IR (OR = 6.120, 95% CI: 2.352–15.926, p < 0.001) in adolescent PCOS patients. Additionally, elevated levels of serum granzyme-B were predictive for increased CV risk in PCOS patients (OR = 0.237, 95% CI: 0.091–0.616, p = 0.003). Conclusions: Increased levels of serum granzyme-B are independently associated with insulin resistance and also with increased CV risk in adolescent polycystic ovary syndrome patients.